2022
DOI: 10.3390/medicina58091284
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Retrospective Analysis of Intradiscal Condoliase Injection Therapy for Lumbar Disc Herniation

Abstract: Background and Objectives: Intradiscal injection of Condoliase (chondroitin sulfate ABC endolyase), a glycosaminoglycan-degrading enzyme, is employed as a minimally invasive treatment for lumbar disc herniation (LDH) and represents a promising option between conservative treatment and surgical intervention. Since its 2018 approval in Japan, multiple single-site trails have highlighted its effectiveness, however, the effect of LDH types, and influences of patient age, sex, etc., on treatment success remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…We initially retrieved 202 ( Figure 1 ) and deleted 96 duplicate articles. A total of 10 articles were included in this study through screening ( Chiba et al, 2018 ; Matsuyama et al, 2018 ; Ishibashi et al, 2020 ; Nakajima et al, 2020 ; Hirai et al, 2021 ; Inoue et al, 2021 ; Okada et al, 2021 ; Banno et al, 2022 ; Kobayashi et al, 2022 ; Oshita et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We initially retrieved 202 ( Figure 1 ) and deleted 96 duplicate articles. A total of 10 articles were included in this study through screening ( Chiba et al, 2018 ; Matsuyama et al, 2018 ; Ishibashi et al, 2020 ; Nakajima et al, 2020 ; Hirai et al, 2021 ; Inoue et al, 2021 ; Okada et al, 2021 ; Banno et al, 2022 ; Kobayashi et al, 2022 ; Oshita et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies included two RCT ( Chiba et al, 2018 ; Matsuyama et al, 2018 ), two prospective ( Inoue et al, 2021 ; Banno et al, 2022 ), and six retrospective studies ( Ishibashi et al, 2020 ; Nakajima et al, 2020 ; Hirai et al, 2021 ; Okada et al, 2021 ; Kobayashi et al, 2022 ; Oshita et al, 2022 ). A placebo was used as a control group in both RCT studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 While it has been reported that higher rates of improvement for lower Pfirrmann classifications, 30 , 31 Oshita et al reported that condoliase appeared more effective for patients with Pfirrmann grade IV compared to grade III patients. 32 , 33 , 34 Regardless of the therapeutic effect of condoliase, we selected patients with Pfirrmann grade III, apart from one of the 12 patients in this study. However, we did not evaluate the action of condoliase on the nucleus pulposus clinically, for example, measurement of the hernia size before and after condoliase administration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were retrieved from three major academic databases (PubMed, Scopus, and Web of Science) using the appropriate search term combinations, including “condoliase” OR “chondroitinase ABC” OR “chondroitin sulfate ABC endolyase” AND “lumbar disc herniation.” Basic research and review articles were excluded. Ultimately, 19 articles were selected, including three randomized controlled trials [ 9 , 10 , 17 ], 14 case series [ 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and two case reports [ 11 , 30 ] ( Figure 2 ). Patient demographics were examined, including age, sex, LDH level, Pfirrmann grade, efficacy rate, and post-treatment surgical rate in patients with LDH treated with 1.25 units of condoliase.…”
Section: Methodsmentioning
confidence: 99%